Machine Guarding Handbook: A Practical Guide to OSHA Compliance and Injury Prevention - Spellman, Frank R.; Whiting, Nancy E. (Government Institutes, 1999)
Machine Guarding Handbook is a must-have reading for safety engineers and managers in manufacturing and other industrial settings who need to incorporate an effective machine guarding safety program, meet OSHA requirements, and protect workers. It provides a basic overview of OSHA's requirements, making compliance easier to achieve, thus preventing the risk of worker injury or mutilation and reducing the occurrence of costly penalties and OSHA audits. This 106-page book explores and discusses the hazards of unguarded machines, common safeguarding methods, the safeguarding of machines and robots, the importance of guarding, the varying methods of machine guarding, training, inspection and maintenance, and safeguarding techniques. In addition, it provides both regulatory information and the material required to implement a viable machine guarding program. Special features include a sample lockout/tagout program, checklists, a machine-guarding case study, chapter summaries, and the complete OSHA Machine Guarding and Lockout/Tagout Standards.